Obelia bidentata Clark 1875 - Peña Cantero, Álvaro L. (Zenodo, 2021)
Obelia bidentata Clark, 1875 Obelia bidentata — Peña Cantero, 2009: 1749, fig. 3g. Material examined. TAN 0602/420 , two stems up to 10 mm high, on S. compressa (NIWA 144251). Ecology and distribution. Obelia bidentata had been collected at depths between 85 and 117 m (Peña Cantero 2009) off Sturge and Buckle islands, epibiotic on H. incertus and in turn as basibiont for colonies of Filellum sp. and L. longitheca . Present material found at a depth of 103−108 m off Sturge Island, growing on S. compressa . : Published as part of Peña Cantero, Álvaro L., 2021, Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica), pp. 321-336 in Zootaxa 4966 (3) on page 326, DOI: 10.11646/zootaxa.4966.3.4, http://zenodo.org/record/4736691 : {"references": ["Clark, S. F. (1875) Descriptions of new and rare species of hydroids from the New England coast. Transactions of the Connecticut Academy of Arts and Sciences, 3, 58 - 66.", "Pena Cantero, A. L. (2009) Benthic hydroids (Cnidaria, Hydrozoa) from the Balleny Islands (Antarctica). Polar Biology, 32, 1743 - 1751. https: // doi. org / 10.1007 / s 00300 - 009 - 0673 - 7"]}